Body Image in Transmen: Multidimensional Measurement and the Effects of Mastectomy. Issue 11 (1st November 2016) - van de Grift, Tim C.; Kreukels, Baudewijntje P.C.; Elfering, Lian; Özer, Müjde; Bouman, Mark-Bram; Buncamper, Marlon E.; Smit, Jan Maerten; Mullender, Margriet G.
ABSTRACT: Introduction: Transmen are generally dissatisfied with their breasts and often opt for mastectomy. However, little is known about the specific effects of this procedure on this group's body image. Aim: To prospectively assess the effect of mastectomy on the body image of transmen, including cognitive, emotional, and behavioral aspects. Methods: During a 10-month period, all transmen applying for mastectomy were invited to participate in this study. The 33 participants completed assessments preoperatively and at least 6 months postoperatively. Main Outcome Measures: Participants were surveyed on body satisfaction (Body Image Scale for Transsexuals), body attitudes (Multidimensional Body-Self Relations Questionnaire), appearance schemas (Appearance Schemas Inventory), situational bodily feelings (Situational Inventory of Body Image Dysphoria), body image-related quality of life (Body Image Quality of Life Inventory), and self-esteem (Rosenberg Self-Esteem Scale). Control values were retrieved from the literature and a college sample. Results: Before surgery, transmen reported less positive body attitudes and satisfaction, a lower self-esteem and body image-related quality of life compared with cisgender men and women. Mastectomy improved body satisfaction most strongly, although respondents reported improvements in all domains (eg, decreased dysphoria when looking in the mirror and improved feelings of self-worth). Most outcome measurements were strongly correlated. Conclusion: Mastectomy improves body image beyond satisfaction with chest appearance alone. Body satisfaction and feelings of "passing" in social situations are associated with a higher quality of life and self-esteem.